The Inhibition of Wnt/Beta-Catenin Signaling Pathway Via Paricalcitol and Pyrvinium Ameliorates Experimental Arthritis - Koca, Suleyman Serdar; Yolbas, Servet; Yildirim, Ahmet; Tektemur, Ahmet; Celik, Zulfinaz Betul; Onalan, Ebru Etem; Akin, Mustafa (Wiley, 2015)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 06-11, 2015 -- San Francisco, CA